Peran Mahasiswa KKN Melalui Lembaga Pengembangan Tilawatil Qur’an dalam Meningkatkan Potensi Anak-Anak di Kelurahan Muara Laung 1 Melalui Seni Baca Al-Qur’an - Annisah Annisah; Nuryadin Cahaya Fadilah; Sonia Sonia; Melsa Anggraini; Ananda Ananda; Akhmad Nor Padilah; Ahmad Bakri; Isra Misra (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
The ability to read the Koran well, correctly (tajwid) and beautifully (qiro'ah) is very important for every Muslim. This research was carried out by involving KKN students who collaborated with this institution to organize interactive and interesting learning programs. The method used is Participation Action Research (PAR). The research results show that this activity not only improves Al-Qur'an reading skills, but also builds children's interest and motivation to learn. In addition, this program has succeeded in involving parents and the community in supporting children's religious education, creating a positive learning environment. Thus, the role of KKN students has proven to be significant in the development of religious education in the community and a significant increase in certain aspects, such as recitation, recitation and interest in reading the Al-Qur'an. This research recommends increasing collaboration between educational institutions and the community for the sustainability of Al-Qur'an-based education programs in the future.